2009
DOI: 10.1073/pnas.0900991106
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of National Fire Plan treatments near the wildland–urban interface in the western United States

Abstract: Because of increasing concern about the effects of catastrophic wildland fires throughout the western United States, federal land managers have been engaged in efforts to restore historical fire behavior and mitigate wildfire risk. During the last 5 years (2004 -2008), 44,000 fuels treatments were implemented across the western United States under the National Fire Plan (NFP). We assessed the extent to which these treatments were conducted in and near the wildland-urban interface (WUI), where they would have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
102
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 17 publications
1
102
0
Order By: Relevance
“…However, when we consider that the great majority of high risk fires started within 2 km of the WUI, it may be argued that an even greater concentration of management near the interface is warranted. When compared to the western USA where only 11 % of treatments were within 2.5 km of the WUI (Schoennagel et al, 2009), prescribed fires as a fuel reduction treatment are well targeted in Sydney (59 % within 2 km).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when we consider that the great majority of high risk fires started within 2 km of the WUI, it may be argued that an even greater concentration of management near the interface is warranted. When compared to the western USA where only 11 % of treatments were within 2.5 km of the WUI (Schoennagel et al, 2009), prescribed fires as a fuel reduction treatment are well targeted in Sydney (59 % within 2 km).…”
Section: Discussionmentioning
confidence: 99%
“…As urban populations expand, so do the number of houses in the WUI in Australia (Hughes and Mercer, 2009) and in the USA (Schoennagel et al, 2009), and house losses increase accordingly (Schoennagel et al, 2009). The probability of loss (consequential risk) is a conditional function of ignition, spread and the vulnerability of urban environments and structures (Bradstock and Gill, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that treatment concentrated close to the assets is more effective for protection than treatments that are more distant (Schoennagel et al 2009;Price and Bradstock 2010). Low fuel age (via fuel treatment) would be expected to reduce fire severity ) and rate of spread (McArthur 1967;McCaw et al 2012), therefore making it more likely that the fire would be slowed before reaching the receiver and more favourable to suppression.…”
Section: Discussionmentioning
confidence: 99%
“…In the western United States, wildfires are becoming more severe, as measured by tree mortality (Westerling et al 2006, Stephens et al 2013). Forest fuel treatments have disproportionately treated the wildland urban interface (WUI), thereby limiting restoration of the broader wildland area (Schoennagel et al 2009) where ecosystem services and timber are at stake. In the WUI, homes and other structures are also at stake, as is human health, and safety of fire fighters and residents (McCaffrey and Olson 2012).…”
Section: Introductionmentioning
confidence: 99%